Un simulador de un modelo poblacional y su caja previsional - Paez Sheridan, P. S. (2020)
By building a system dynamics simulation platform from a demo-graphic model, this document analyzes the behavior of the population over time, as well as the population of the social security system. Simulation results show that there will be different types of problems in the future and will allow the Government to anticipate them. Due to the simplicity of its construction, it is very easy to implement in different regions with different precepts.